Chlorophyll fluorescence emission as a reporter on cold tolerance in Arabidopsis thaliana accessions - Mishra, Anamika; Mishra, Kumud B; Höermiller, Imke I; Heyer, Arnd G; Nedbal, Ladislav (Plant signaling & behavior, 2011)
Non-invasive, high-throughput screening methods are valuable tools in breeding for abiotic stress tolerance in plants. Optical signals such as chlorophyll fluorescence emission can be instrumental in developing new screening techniques. In order to examine the potential of chlorophyll fluorescence to reveal plant tolerance to low temperatures, we used a collection of nine Arabidopsis thaliana accessions and compared their fluorescence features with cold tolerance quantified by the well established electrolyte leakage method on detached leaves. We found that, during progressive cooling, the minimal chlorophyll fluorescence emission rose strongly and that this rise was highly dependent on the cold tolerance of the accessions. Maximum quantum yield of PSII photochemistry and steady state fluorescence normalized to minimal fluorescence were also highly correlated to the cold tolerance measured by the electrolyte leakage method. In order to further increase the capacity of the fluorescence detection to reveal the low temperature tolerance, we applied combinatorial imaging that employs plant classification based on multiple fluorescence features. We found that this method, by including the resolving power of several fluorescence features, can be well employed to detect cold tolerance already at mild sub-zero temperatures. Therefore, there is no need to freeze the screened plants to the largely damaging temperatures of around -15°C. This, together with the method's easy applicability, represents a major advantage of the fluorescence technique over the conventional electrolyte leakage method.
Keywords: Electrolytes; nízká teplota; Stress, Physiological; fluorescence; chlorofyl; elektrolyty; aklimatizace; fyziologický stres; Arabidopsis; Fluorescence; Cold Temperature; Chlorophyll; Acclimatization